EFEKTIFITAS BIMBINGAN KLIEN NARKOTIKA OLEH BALAI PEMASYARAKATAN KELAS I PADANG UNTUK MENCEGAH TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Yazrul, Ade; Faniyah, Iyah (LPPM Universitas Ekasakti Padang, 2019)
The implementation of narcotics client guidance by Community Guidance to prevent criminal acts of narcotics abuse is regulated in the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics and Law of the Republic of Indonesia Number 12 of 1995 concerning Correctional Clients Guidance in practice is still a lot of dependence on narcotics. Based on the results of the study, it can be concluded that: First, the role of Bapas Class I Padang Community Supervisor in guiding clients of narcotics abuse has been carried out well, because the guidance provided by Bapas Class I Padang Community Supervisor is in the form of Post-Rehabilitation Program which is a follow-up stage given to narcotics addicts after undergoing rehabilitation which aims to guide the narcotics client to develop attitudes to society and not repeat it again. Secondly, the effectiveness of narcotics clients in preventing narcotics criminal acts at Padang Class I Correctional Facilities in principle can be said to be quite effective because every client who follows the Post-Rehabilitation Program does not have a client who repeats narcotics abuse. Third, Constraints faced in Narcotics Client Guidance at Padang Class I Correctional Institution are limited conditions and functions and lack of Human Resources (HR), as well as clients who have undergone rehabilitation to undergo post-rehabilitation services, many who have not been serious about recovering, because of the lack of family and community support in realizing the recovery of former addicts, and the lack of a place to channel their interests and potential to return to the social environment of the community. In addition, the demands of the client's economic needs become an element of strengthening the absence of clients because they cannot leave their jobs which are mostly from the private sector. Besides that, budget problems are an important factor in post-rehabilitation implementation in order to run optimally.